2021
DOI: 10.21037/apm-21-378
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interval training with non-invasive ventilation in severe chronic obstructive pulmonary disease—a prospective cohort study with matched control group

Abstract: Background: In severe chronic obstructive pulmonary disease (COPD), interval training (IT) can be performed with oxygen support, which provides beneficial effect on metabolic processes, tissue perfusion, and peripheral muscle function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Also, Greulich et al [ 38 ] and Hsiao et al [ 39 ] stated a considerable improvement in CAT score in the group receiving O 2 therapy, demonstrating the importance of oxygen supplementation during the exercise training in relieving the symptoms. Fekete et al [ 40 ] and Fakharian et al [ 41 ] found that the NIV group had significant CAT score improvement compared with the control group (PR group without NIV). Also, Borghi-Silva et al [ 17 ] concurred with our results as they stated that QoL had more significant improvement in the NIV group than O 2 supplementation group.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Greulich et al [ 38 ] and Hsiao et al [ 39 ] stated a considerable improvement in CAT score in the group receiving O 2 therapy, demonstrating the importance of oxygen supplementation during the exercise training in relieving the symptoms. Fekete et al [ 40 ] and Fakharian et al [ 41 ] found that the NIV group had significant CAT score improvement compared with the control group (PR group without NIV). Also, Borghi-Silva et al [ 17 ] concurred with our results as they stated that QoL had more significant improvement in the NIV group than O 2 supplementation group.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 50% of premature deaths are linked to lifestyle, such as our diet [ 111 ]. A diet can be characterized quantitatively, by its calorie content, or qualitatively, for example, by its macro- and micronutrient content.…”
Section: Dietary Factors Influencing Mortalitymentioning
confidence: 99%
“…However, it is essential that chronic lung patients adhere to medication and medication monitoring instructions, with regular preventive inhaled bronchodilator medication being of particular importance [32]. It is important to avoid smoking completely and to maintain regular physical activity [33,34]. Most patients are given long-acting bronchodilators or a combination of different types of bronchodilators in their inhalers (so-called "sprays" or "dry powder inhalers"), and abandoning these preparations is particularly dangerous [35].…”
Section: Treatment Of Copd Patients Infected With Covid-19mentioning
confidence: 99%